Examining Determinants of Health Service Utilisation among Filipino Older People: A Cross-Sectional Study - Cotingting, Crystle T (Archīum Ateneo, 2018)
Objective This study was done to study, using Andersen's Behavioral Model, factors affecting health service utilisation among older Filipinos. Methods A total of 237 older people from Marikina City, Philippines, were randomly selected and surveyed face-to-face on factors affecting health service utilisation, specifically age, civil status, educational level, employment status, sex, health insurance coverage, household income, chronic disease status and perceived health status. Results Seventy-nine per cent had used health services in the past year (mean: 5.7 visits per year). Female sex and having a chronic disease were significantly associated with health service utilisation. The odds of using health services was 3.1 times higher for those who had a chronic disease and 2.2 times higher for female sex, assuming all other variables are held constant. Conclusion Findings of this study support targeting men in health promotion campaigns and implementing population-based, chronic disease screening programs to improve the reach of health services among Filipino older people.